Fish consumption is associated with school performance in children in a non-linear way: Results from the German cohort study KiGGS. Issue 1 (23rd December 2019) - Lehner, A; Staub, K; Aldakak, L; Eppenberger, P; Rühli, F; Martin, R D; Bender, N
Abstract: Introduction: How the long-chain fatty acids docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) in the diet permitted human brain evolution, and how much our brains need today to function optimally are still hot topics for debate. DHA and EPA are considered as semi-essential because only insufficient amounts can be produced from other nutrients, such that they must be ingested with the diet. However, the Dietary Reference Intake of DHA and EPA, or of fish containing these fatty acids, has not yet been established. Eating fish is often recommended and generally considered beneficial for health and cognitive development in children and adolescents. For this study, data from a large cohort study were analysed to assess the association between fish consumption and cognitive school performance in children and adolescents. Methods: Data from the German cohort of children and adolescent health KiGGS, which was conducted 2003–06 and included more than 17 000 children, were analysed. Ordered logistic regressions were performed to test for associations between fish intake and school performance. Potential confounders were included in the models. Results: A statistically significant association was found between an intake of 8 g of fish per day and the probability of increasing the final grade in German [odds ratio (OR) 1.193, 95% confidence interval (CI) 1.049–1.358] and mathematics (OR 1.16, 95% CI 1.022–1.317) by one point, compared to no or very limited fish consumption. For the outcome German, higher levels of fish intake also showed a positive effect. These relationships were not linear but tended to decrease again at higher doses of fish. Discussion: Our result confirms previous reports of a positive association between fish intake and school performance. Interestingly, this relationship was not linear but tended to decrease again in the highest categories of fish intake. We hypothesize that mercury or other pollutants in the fish could be detrimental at high levels. As only half of all children met the minimal fish intake recommendations, fish consumption should be promoted more strongly in children to meet the minimal requirements of long-chain polyunsaturated fatty acids. Lay Summary: Polyunsaturated fatty acids like DHA and EPA that are present in fish are essential for a healthy human brain development. We found a U-shaped association between fish intake and school performance in children. We hypothesize that mercury or other pollutants in the fish could be detrimental at high intake levels.